Melanoma development : Molecular biology, genetics and clinical application - Bosserhoff, Anja-Katrin (Springer, 2017)
This book focuses on malignant melanoma, discussing the current state of scientific knowledge and providing insights into the underlying basic mechanisms, the molecular changes, genetics and genomics. Human Melanoma is a dangerous type of skin cancer affecting an increasing population, and a better understanding of its development will help in finding sophisticated targeted therapies. The second revised edition features the latest research findings and offers updates on the latest advances and potential novel melanoma therapies. It is a valuable resource for researchers and clinicians working in the fields of melanoma, cancer research and therapy as well as dermatology.- Resumé vydavatel
Keywords: melanomy; rakovina kůže; melanomas; skin cancer; elektronické knihy; sborníky; electronic books; papers of several authors